2014
DOI: 10.1111/apt.12869
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab drug and antibody levels as predictors of clinical and laboratory response in patients with Crohn's disease

Abstract: SUMMARY BackgroundAdalimumab is an effective treatment for Crohn's disease (CD). Antiadalimumab antibodies (AAA) and low trough serum drug concentrations have been implicated as pre-disposing factors for treatment failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(107 citation statements)
references
References 30 publications
6
96
0
4
Order By: Relevance
“…FC is a highly accurate predictor of endoscopic activity in patients with IBD, and low FC (FC < 100 µg/g) was found to have a high correlation with clinical, endoscopic, and histological remission [17,19]. Our group reported a recent study in which serum adalimumab (ADL) levels were associated with the normalization of CRP and FC, with the drug levels being higher for patients with normal FC levels [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FC is a highly accurate predictor of endoscopic activity in patients with IBD, and low FC (FC < 100 µg/g) was found to have a high correlation with clinical, endoscopic, and histological remission [17,19]. Our group reported a recent study in which serum adalimumab (ADL) levels were associated with the normalization of CRP and FC, with the drug levels being higher for patients with normal FC levels [18].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that higher levels of anti-TNF drugs are detected in patients with lower FC and CRP [18,19]. In this study, we aimed to investigate the association of laboratory factors (including CRP and FC) and serum concentrations of IFX during induction treatment with primary nonresponse in patients with active CD to predict to what extent pharmacokinetic and inflammatory parameters can influence the clinical outcome of IFX induction therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In inflammatory bowel disease a cut-off trough M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT level between 3 and 5.8 µg/ml for adalimumab may have the optimal sensitivity, specificity and positive likelihood ratio for prediction of clinical response. 48,88 In general, high serum concentrations of anti-TNF agents, measured just before the administration of the next dose, are associated with clinical improvement, whereas low levels are associated with poor responses. 7,26 All exogenous proteins are capable to induce immunogenicity.…”
Section: Serum Drug Levels and Anti-drug Antibodiesmentioning
confidence: 99%
“…The random-effects pooled estimate for the prevalence of LOR was 0.435 (95% CI 0.330 to 0.540); this is likely to be an overestimate owing to double-counting of patients from the Mazor et al 108 study. Given the meta-analysis values and the sensitivity, specificity and prevalence values, the point estimate for the probability of positive and negative test results is 0.253 (range 0.212-0.293) and 0.747 (range 0.707-0.788), respectively.…”
Section: Specificity (95% Ci)mentioning
confidence: 89%
“…108 reported results by test rather than by patient (there were 118 tests in 71 patients; authors stated that using the first test result for each patient did not alter the results). Sensitivity and specificity pairs are summarised in Figure 42. A single study of patients with LOR was identified 84 (as shown in Figure 43).…”
Section: Specificity (95% Ci)mentioning
confidence: 99%